PELATIHAN PENINGKATAN KEMAMPUAN MEMBACA KITAB KUNING SANTRI MELALUI PROGRAM BK (BAHSUL KUTUB) DI DAYAH NAHDHATUL ULUM KEC. SYAMTALIRA BAYU - Sulaiman, Sulaiman; Mustafa, Mustafa (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2022)
Dayah is an educational institution that focuses on the field of religion, especially in the field of spiritual education and character development. Each Dayah has their own method of nurturing and developing the talents and interests of their students, especially in the area of ​​reading the yellow book. Dayah is a non-formal educational institution that still uses traditional educational methods. So in this study, the researchers wanted to introduce a new method to improve the ability to read the yellow book for santri in the Nahdhatul Ulum Dayah Kec. Syamtalira Bayu. The research method is in the form of qualitative with the type of literature study is descriptive and uses a person instrument. The results showed that the BK program (bahsul pole) in Dayah Nahdhatul Ulum used three learning methods, namely the halaqah method, memorization, and deliberation. There was a problem as well as a wise solution that was applied by the teacher council at the beginning of the introduction of this program, so that the program became a ray of light for the santri in the Nahdhatul Ulum Dayah, considering that after this program the students had begun to understand the yellow book well, have a polite attitude, think critical, responsible for expressing opinions, respecting the opinions of others and having the courage to take part and appear in public to solve religious problems.